The Impact of Digital Finance on Corporate Green Innovation - Chen, Zhen; Zhang, Gaohan (International Journal of Social Sciences and Public Administration, 2024)
This paper discusses the impact of digital finance on corporate green innovation. Digital finance greatly promotes the development of corporate green innovation by providing convenient financing channels, reducing financing costs, and improving the efficiency of capital utilization. Utilizing big data and artificial intelligence technology, enterprises are able to better manage and control risks, thus improving the success rate of green innovation projects. In addition, digital finance also reduces information asymmetry, optimizes resource allocation, and improves the efficiency and effectiveness of green innovation through information transparency and data analysis. This paper analyzes the successful case of Tesla to reveal the key role of digital finance in green innovation, and puts forward corresponding suggestions for policy support and corporate strategy adjustment to promote the sustainable development of green economy.